Serat Wirid Hidayat Jati and the Development of Javanese Islam in the 19th-20th Century - Triatmo, Bambang; Sudardi, Bani (Institut Agama Islam Sunan Giri (INSURI) Ponorogo, 2025)
This study explores Wirid Hidayat Jati, a composition by Raden Ngabehi Ranggawarsita finalized in 1862, and its role in shaping Javanese Islam during the 19th and early 20th centuries. The text incorporates Sufi doctrines, particularly the principle of manunggaling kawula Gusti (the union of humanity with the Divine), which is closely related to the concept of martabat tujuh (seven dignities) in Sufi tradition. Employing a historical research design and textual analysis, this study collected data from primary sources, namely the Wirid Hidayat Jati manuscript, as well as secondary sources such as historical records, pesantren archives, and scholarly works. The data were analyzed using content analysis and historical interpretation to identify core mystical and ethical themes and to examine their influence on the religious practices of Javanese Islam. The findings reveal that Wirid Hidayat Jati, through its reading, teaching, and interpretation by santri and Ranggawarsita’s followers, contributed to the dissemination of Sufism and reinforced practices that harmonized Islamic principles with Kejawen values. As a spiritual guide, the text not only influenced devout Muslims (santri) but also adherents of Kejawen, and its impact continued into the early 20th century. In conclusion, Wirid Hidayat Jati reflects Ranggawarsita’s Sufi philosophy and demonstrates the formation of a distinct Javanese Islamic identity characterized by adaptability and cultural syncretism.